Administration of imatinib mesylate in rats impairs the neonatal development of intramuscular interstitial cells in bladder and results in altered contractile properties. Issue 4 (24th April 2013) - Gevaert, Thomas; Hutchings, Graham; Everaerts, Wouter; Prenen, Hans; Roskams, Tania; Nilius, Bernd; De Ridder, Dirk
Abstract Aims The KIT receptor is considered as a reliable marker for a subpopulation of interstitial cells (IC), and by persistent neonatal inhibition of KIT we have investigated the role of this receptor in the development of IC‐networks in bladder and we have observed the functional consequences of this inhibition. Methods Newborn rat pups were treated daily with the KIT inhibitor imatinib mesylate (IM). After 7 days animals were sacrificed and bladder samples were dissected for morphological and functional studies. Morphological research consisted of immunohistochemistry with IC specific antigens (KIT and vimentin) and electron microscopy. The functional studies were based on isolated bladder strips in organ baths, in which spontaneous bladder contractility and the response to a non‐subtype selective muscarinic agonist was evaluated. Results Suburothelial and intramuscular IC were found and characterized in neonatal rat bladder. IM‐treatment induced a significant decrease in numbers of IC based on specific immunohistochemical markers, and electron microscopy revealed evidence of IC cell injury. These morphological alterations were observed on intramuscular IC only and not on IC in the suburothelium. Isolated muscle strips from IM‐treated animals had a lower contractile frequency and an altered response to muscarinic agonists. Conclusions The present study shows the presence of regional subpopulations of IC in neonatal rat bladder, provides evidence for a dependence on KIT of the development of intramuscular IC and supports the hypothesis that a poor development of networks of intramuscular IC might have repercussions on spontaneous and muscarinic‐induced bladder contractility. Neurourol. Urodynam. 33:461–468, 2014. © 2013 Wiley Periodicals, Inc.